What are we missing? a qualitative exploration of sexual agency and the related behaviours of AGYW in two HIV interventions in South Africa. - Fowler, Chantal (Department of Public Health and Family Medicine, 2025)
In Sub-Saharan Africa, Adolescent Girls and Young Women (AGYW) aged 15-24 years bear a significant HIV prevalence rate of 20.6%. Additionally, AGYW experience a disproportionate burden, being 3.3 times more likely to contract HIV compared to their male counterparts. This group has remained a key focus for global HIV interventions, yet high incidence has been sustained. While several contributing social, behavioural, and structural factors have been identified, research suggests that interventions may not sufficiently address complexities located within the lived experiences of intervention beneficiaries. Some of these less explored areas within lived experience of sexual agency and subsequent behaviour choices may be contributing to the sustained incidence but may be less understood due to a lack of research that adopts a lens prioritising this focus. The legacy of colonial history in the study of sexuality in Africa may also be contributing to this sustained incidence. This research adopted a qualitative approach to explore experiences of AGYW navigating sexual decision-making and who meet the criteria for being recipients of two large-scale HIV reduction interventions — one of which is one of the largest HIV interventions for AGYW in the world. Methods: I used Critical Discourse Analysis (CDA) to conduct a document review of programmatic documents of the two interventions outlining specific details of the background of the programme, its programme design, implementation, service delivery and monitoring and evaluation. Further to this, I used thematic analysis to analyse twenty nine interviews with AGYW, teachers, and implementers who lived and worked in intervention sites across South Africa, and who met the criteria for intervention (n=29). These interviews were comprised of a combination of primary and secondary data. I worked in the process evaluations of two large HIV interventions and used transcripts that were generated during this work as secondary data, as they provided data that was relevant to my PhD questions. I also conducted interviews with participants whom I sourced from my work with these evaluations which comprised my primary data set. Results: The document review revealed that the two interventions frame AGYW as lacking in knowledge and unable to enact agency. Further to this, they are described as being too concerned with daily priorities which compete with Sexual and Reproductive Health (SRH) priorities. These ‘misplaced' priorities are what is problematised in the narrative, with the burden for change being placed on AGYW to shift them. Interviews with AGYW and community members revealed that advice from parents, teachers and interventions about sex is experienced largely as warnings about the dangers of sex and chastisement to “stay away from boys”; messages grounded in the sex- negative paradigm. As a result, AGYW express feelings of shame and fear of judgement if they are seen to be sexually active and subsequently attempt to hide their sexual activity. AGYWs' agency in sexual decision-making is diminished as they are afraid of shaming and judgement from adult caregivers should they try to enact sexual agency by accessing HIV prevention services for example. AGYW reported personal experiences of sex to be positive, resulting in peers encouraging each other to have sex and to ignore the warnings of adults, leaving AGYW confused and ambivalent as to which messages to believe and act on. I assert that as researchers, we need to better understand the experience of AGYW trying to adopt more sex positive attitudes in a context so heavily shrouded in sex negative paradigms. I offer suggestions around the need to create social structural conditions that can facilitate and support AGYW in their development of sexual agency. I conclude that currently, intent is not strong enough to shift toward a more decolonised approach to sexual empowerment of AGYW due to colonial legacies that persist in public health discourse and rhetoric around SRH.